“Will the Real Semi-Speaker Please Stand Up?” Language Vitality, Semi-Speakers, and Problems of Enumeration in the Canadian North - Boltokova, Daria (Anthropologica, 2017)
This article reassesses categories used in language revitalisation efforts and critiques some enumeration practices that language activists use to measure language endangerment and vitality. Drawing on ethnographic fieldwork in the Dene Tha settlement of Chateh in northwestern Alberta, Canada, I argue that the practices of speaker enumeration are often premised on idealised notions of who counts as an endangered language speaker. Standard methods for counting endangered language speakers fail to capture the heterogeneous linguistic practices of partially fluent “semi-speakers,” who often constitute the majority of young speakers in endangered language communities. To correct this oversight, I propose shifting the discourse of language endangerment toward one of language vitality, enabling semi-speakers to be recognised and counted as rightful, valid speakers of endangered languages.